ADMINISTRATIVE-MANAGEMENT BODIES AND PUBLIC ORGANIZATIONS ACTIVITIES IN NATURAL DISASTERS - V. S. Semenov; O. V. Semenova (Современная наука и инновации)
The article examines and evaluates the activities of administrative structures, companies and public organizations in the process of preventing and localizing the consequences of natural hazards.